An analysis of Kevin's ego in "Split" movie - A Psycoanalysis Study - Deni Pratama; Merry Rullyanti (Literary Criticism, 2020)
Split movie is an interesting psycholinguistically analyzed movie in the last decade. The movie criticizes a bad psychological relationship between the main character and his community. Through this study, the researcher analyzed the multiple personality of main character on Split movie and used the theory of Sigmund Freud within the title “An Analysis of Kevin’s Ego in “Split” Movie (a Psychoanalysis Study)”. The purpose of this study are to find out Kevin’s ego based on the Sigmund Freud’s defence mechanism in the movie and to find out Kevin’s most frequently emerging ego based on the Sigmund Freud’s defence mechanism. In this study the researcher used a qualitative descriptive method by collecting data on all character conversations in “Split” movie. The data were analyzed based on Frued's theory of defence mechanism. Furthermore, the data were also anaylized by using Spradley's theory. There are three steps that must be taken in using this theory, namely domain analysis, taxonomic analysis and component analysis. The researcher found 8 Kevin’s egos that got involved in real dialogues in Split movie. They are childish, firm man, mother-like, effeminate person, firm and effeminate, cruel, cool man, and weak lady. The highest val ue of frequently emerging ego goes to childish. Whereas, the lowest frequently emerging ego is a weak lady. Hopefully, the results of this study will increase the knowledge in English letters, especially in psychoanalysis study about various egos of movie characters or even real persons and the defence mechanism based on Sigmund Freud’s and Spradley’s theories.